Hearing loss and its association with all-cause and cause-specific mortality: A meta-analysis of cohort studies - Jinli Jia; Hongyan Li; Chunlan Xu (PLoS ONE, 2025)
Background This study aimed to examine the epidemiological associations between hearing loss and the risk of all-cause mortality, cardiovascular mortality, and cancer mortality. Methods A comprehensive search was performed in PubMed, Cochrane Library, and Embase for cohort studies published from database inception to January 12, 2025, using relevant MeSH terms and keywords. Study quality was assessed using the Newcastle-Ottawa Scale (NOS). A random-effects model was applied for the meta-analysis. Sensitivity analysis was conducted by sequentially excluding individual studies to assess the robustness of the results. Subgroup analyses were performed based on hearing function measurement methods, study design, and continent. Publication bias was evaluated using funnel plots and Egger’s test. Statistical analyses were conducted using Stata 14.0. Results This meta-analysis included 36 cohort studies with a total of 6,364,914 participants, published between 1992 and 2024. Hearing loss was significantly associated with all-cause mortality (HR: 1.21; 95% CI: 1.13–1.31; I² = 95.7%, P < 0.001), cardiovascular mortality (HR: 1.22; 95% CI: 1.12–1.33; I² = 52.4%, P < 0.001), and cancer mortality (HR: 1.11; 95% CI: 1.02–1.22; I² = 51.2%, P = 0.016), after adjusting for demographics and comorbidities. Subgroup analysis showed that audiometrically measured hearing loss had a stronger effect than self-reported hearing loss (HR: 1.28; 95% CI: 1.10–1.49; I² = 97.7%, P = 0.002). The risk of all-cause mortality was higher in prospective cohorts compared to retrospective cohorts (HR: 1.24; 95% CI: 1.05–1.46; I² = 97.2%, P = 0.012). Additionally, the risk of all-cause mortality was slightly higher in studies from Asia compared to other continents (HR: 1.33; 95% CI: 1.09–1.62; I² = 98.3%, P = 0.005). Conclusions Our meta-analysis indicates that hearing loss is associated with an increased risk of all-cause, cardiovascular, and cancer mortality. Healthcare providers managing patients with hearing loss should consider its potential impact on overall health and longevity. PROSPERO registration number CRD 42025637635